Natural Plasmodium infection in wild macaques of three states in peninsular Malaysia - Amirah, Amir; Shahhaziq, Shahari; Jonathan Wee Kent, Liew; Jeremy Ryan, de Silva; Mohammad Behram, Khan; Meng Yee, Lai; Georges, Snounou; Mohd Lutfi, Abdullah; Millawati, Gani; Jeffrine J., Rovie-Ryan; Yee-Ling, Lau (ELSEVIER, 2020)
Zoonotic cases of Plasmodium knowlesi account for most malaria cases in Malaysia, and humans infected with P. cynomolgi, another parasite of macaques have recently been reported in Sarawak. To date the epidemiology of malaria in its natural Macaca reservoir hosts remains little investigated. In this study we surveyed the prevalence of simian malaria in wild macaques of three states in Peninsular Malaysia, namely Pahang, Perak and Johor using blood samples from 103 wild macaques (collected by the Department of Wildlife and National Parks Peninsular Malaysia) subjected to microscopic examination and nested PCR targeting the Plasmodium small subunit ribosomal RNA gene. As expected, PCR analysis yielded significantly higher prevalence (64/103) as compared to microscopic examination (27/103). No relationship between the age and/or sex of the macaques with the parasitaemia and the Plasmodium species infecting the macaques could be identified. Wild macaques in Pahang had the highest prevalence of Plasmodium parasites (89.7%), followed by those of Perak (69.2%) and Johor (28.9%). Plasmodium inui and P. cynomolgi were the two most prevalent species infecting the macaques from all three states. Half of the macaques (33/64) harboured two or more Plasmodium species. These data provide a baseline survey, which should be extended by further longitudinal investigations that should be associated with studies on the bionomics of the anopheline vectors. This information will allow an accurate evaluation of the risk of zoonotic transmission to humans, and to elaborate effective strategies to control simian malaria.